BIOINOCULANTS FOR COIR RETTING - A. N. Ravindranath; U. S. Sarma (International Coconut Community Journal, 1995)
The mesocarp of the coconut or its husk is the source of coir. Coir fibre has several potential end uses like for the manufacture of various coir products predominantly coir floor coverings, yarn, rope, rubberized coir and latest as geotextile material. Coir is extracted from the coconut husk which is subjected to steeping in saline backwaters for six to nine months. This prolonged period of steeping is disadvantageous on economic considerations and also deprives the coir industry of sufficient raw material for the product sector. The treatment of selected strains of phenol degrading bacterial cultures on to husks immersed for retting is reported to reduce the period of retting to some extent 3. This paper reports the findings of a field study on the treatment of selected strains of bacteria on one lakh husks steeped for retting. Samples of husks drawn out after three months of steeping were observed to be fully retted and yielded fibre suitable for spinning superior quality coir yarn.